Tsunami impacts on shallow groundwater and associated water supplies on the east coast of Sri Lanka - Villholth, Karen G.; Amerasinghe, Priyanie H.; Jeyakumar, P. (2008)
In order to assess the immediate and intermediate impacts of the December 26, 2004 tsunami on groundwater and associated water supply on the east coast of Sri Lanka, a monitoring program, focusing on domestic drinking water wells, was conducted in three study areas in the period March to July, 2005. The areas investigated were overlaying shallow, unconfined sandy aquifers, and the topography was flat. A total of 150 wells were monitored, covering both affected (inundated by tsunami water) and unaffected wells. Results indicate that wells were affected by salinity intrusion to various degree between the sites and within sites, up to 1.5 km inland. Thirty nine percent of all monitored wells had been flooded within a distance of 2 km from the coastline. Salinity levels after seven months after the tsunami were above a defined drinking water acceptability criterion (1000 ?S/cm) in the majority of the affected, tsunami-flooded wells (91%). Excess salinity in wells is expected to persist for at least one more monsoon season.